PENINGKATAN KEMAMPUAN MENGIDENTIFIKASI UNSUR INTRINSIK HIKAYAT DENGAN TEKNIK ECOLA SISWA SMA SINAR KASIH SINTANG - Evanirmala, Sanggar; Syam, Christanto; Priyadi, A Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstarctThe background of this research is the low ability of the students in identifying intrinsic element of saga caused by difficulties in mastering a content of a saga text. Formulation of the problem in this research is Ecola techniques can improve saga discovery learning on students of class X D of Sinar Kasih Senior High School Sintang. The purpose of this research is to describe improvement identify intrinsic element of saga with Ecola techniques on students of class X D of Sinar Kasih Senior High School Sintang. The scope of this research is students of class X D Sinar Kasih Senior High School Sintang. The method used in this research is descriptive and the type of research used in this research is qualitative. Research subjects are students of class X D with the number of 21 students of Sinar Kasih Senior High School Sintang. This form of research is carried out in the form of classroom action research. Data collection technique is carried out by observation and measurement/test techniques. Learning planning identify intrinsic element of saga cycle I got result 63%, cycle II got result 79% and cycle III got result 86%. The implementation of learning identified intrinsic elements with ecola techniques in the first cycle of the first meeting to got result 61% and the second meeting got result 60%. The second cycle, it increased on the first meeting got result 76% and on the second meeting it increased from previous cycle which got result 76%. On the cycle III of first meeting it increased 89% and on the second meeting it got result 93%. The average value of students in the first cycle reached 63. The results of the average value in the second cycle increased by 73, and it increased good enough in cycle III with an average value of 79.        Keywords: Enhancement, Intrinsic element of saga, Extending concept through  Language activities technique